”Just-in-time teaching” in undergraduate mathematics - Juter, Kristina; Olsen, Jan-Fredrik (NOMAD Nordic Studies in Mathematics Education, 2014)
We compared five groups of students to investigate the effects of ”Just-in-time teaching” (JiTT), a method designed to both help students keep up with the often fast pace of undergraduate calculus and to deepen their learning. In total, 137 students participated in the study. The outcome is discussed in terms of conceptual and procedural knowledge in relation to examination and other assessment tasks. We observed an improvement on the assessed items and a shift in study habits.